Study of Inheritance Patterns of Morphological-Agronomic Properties on F2 Results of Local Rice Red Sikin with Ciherang Varieties - susy siahaan (Jurnal Agroekoteknologi Tropika Lembab, 2018)
Utilization effort sof local red rice germ plasm of East Kalimantan isconducted by cross-breeding research between local rice Sikin Merah as female elders with Ciherang varieties as male elders. This study aims to determine the pattern of inheritance of plant height, age, number of grains per panicle and panicle length, and the color of rice in the population of F2 generation plants. There search started from October 2016 until March 2017, in the tidal rice field of Sidomulyo Village, Anggana Subdistrict, Kutai Kartanegara Regency. The F2 identification method used wasasing le planting selection method, based on the Characterization and Evaluation of Rice Crops System Guidance. Testing the conformity of expectation value, used Chi-Square test (χ2), and to see the pattern of character inheritance tested by Mendel genetic analysis. The results showed that the pattern of character inheritance of plant height character and plant age character followed the ratio 9:7 in heritance pattern with double recessive epistasis gene action, inheritance of rice color character followed the ratio 3:1 pattern of inheritance pattern with the action of the simple genic gene, character inheritance the number of grain per panicle followed the ratio of the inheritance pattern 15:1 with the action of the double dominant epistasis gene, and the inheritance of  the length of panicle character followed the ratio 3:1 inheritance pattern with the action of the dominant gene.